Modular Molecular Weaponry Plays a Key Role in Competition Within an Environmental Vibrio cholerae Population - Hussain, Nora A. S.; Kirchberger, Paul C.; Case, Rebecca J.; Boucher, Yann F. (Frontiers in Microbiology, 2021)
The type VI secretion system (T6SS) operons of Vibrio cholerae contain extraordinarily diverse arrays of toxic effector and cognate immunity genes, which are thought to play an important role in the environmental lifestyle and adaptation of this human pathogen. Through the T6SS, proteinaceous “spears” tipped with antibacterial effectors are injected into adjacent cells, killing those not possessing immunity proteins to these effectors. Here we investigate the T6SS mediated dynamics of bacterial competition within a single environmental population of V. cholerae. We show that numerous members of a North American V. cholerae population possess strain-specific repertoires of cytotoxic T6SS effector and immunity genes. Using pairwise competition assays, we demonstrate that the vast majority of T6SS-mediated duels end in stalemates between strains with different T6SS repertoires. However, horizontally acquired effector and immunity genes can significantly alter the outcome of these competitions. Frequently observed horizontal gene transfer events can both increase or reduce competition between distantly related strains by homogenizing or diversifying the T6SS repertoire. Our results also suggest temperature-dependent outcomes in T6SS competition, with environmental isolates faring better against a pathogenic strain under native conditions than under those resembling a host-associated environment. Taken altogether, these interactions produce density-dependent fitness effects and a constant T6SS mediated arms race in individual V. cholerae populations, which could ultimately preserve intraspecies diversity. Since T6SSs are widespread, we expect within-population diversity in T6SS repertoires and the resulting competitive dynamics to be a common theme in bacterial species harbouring this machinery.